Investigating English as Foreign Language learners on Learning Morphology in English Language Curriculum - Etika Dewi Kusumaningtyas; Endang Susilowati (Universitas An Nuur, 2023)
This research in title “Investigating English as Foreign Language learners on Learning Morphology in English Language Curriculum”. linguistics provides a system that convey construction of language that used by learner appropriate to the categories. The learners required to know the basic language information which is needed in process of using. Morphology exposes the learners to fresh morphemes, which broadens your vocabulary and teaches you fresh words. This research aims to uncover EFL learner on learning morphology and explore the morphology subject classes on students’ belief. The researcher used descriptive qualitative approach. Thus, conducting morphology classes by using case or project-based method assisted the learner to analyzed and figured out the process of language in use.